2019
DOI: 10.29399/npa.23646
|View full text |Cite
|
Sign up to set email alerts
|

12/15 Lipoxygenase as a Therapeutic Target in Stroke

Abstract: Lipoxygenases are a family of lipid-oxidizing enzymes, which generate eicosanoids and related compounds from arachidonic acid and other polyunsaturated fatty acids. These metabolites play important roles in physiology and pathogenesis of host defense mechanisms, cardiovascular diseases, cancer, inflammatory, allergic and neurodegenerative diseases. The 12/15-lipoxygenase (LOX) is special in that it can directly oxidize lipid membranes containing polyunsaturated fatty acids, without the preceding action of a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…LOX activity, particularly the 12/15-LOX isoform, is enriched in leukocytes, which contributes to oxidative injury in the brain. 148 In experimental SAH, 12/15-LOX is increased in macrophages adjacent to the subarachnoid blood, and its inhibition and gene deletion decrease brain injury and improve short-term functional outcome after SAH. 149 Another study reported increased neuronal expression of 5-LOX‚ with 5-LOX inhibition reducing neuroinflammation and neuronal cell death after experimental SAH.…”
Section: Inflammation In the Development Of DCImentioning
confidence: 99%
“…LOX activity, particularly the 12/15-LOX isoform, is enriched in leukocytes, which contributes to oxidative injury in the brain. 148 In experimental SAH, 12/15-LOX is increased in macrophages adjacent to the subarachnoid blood, and its inhibition and gene deletion decrease brain injury and improve short-term functional outcome after SAH. 149 Another study reported increased neuronal expression of 5-LOX‚ with 5-LOX inhibition reducing neuroinflammation and neuronal cell death after experimental SAH.…”
Section: Inflammation In the Development Of DCImentioning
confidence: 99%
“…Lipoxygenases (LOX) are a family of enzymes responsible for the oxidation of lipids and the generation of a range of metabolites such as eicosanoids and PUFA-related compounds. These metabolites play diverse physiological and pathological roles in inflammatory, neurodegenerative, and cardiovascular diseases, as well as, in defence mechanisms [ 20 , 21 ]. Lipoxygenases have also been reported in cell differentiation [ 22 , 23 ], apoptosis [ 24 ], and play an important role in the immune response by helping to regulate cytokine secretion [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…12/15-LOX is found to be upregulated after stroke, resulting in neuronal death and leakage of BBB and BRB [ 134 ]. Inhibition of 12/15-LOX was also shown to reduce infarct volume and edema in the stroke area, suggesting its potential role as an effective and viable therapeutic option for ischemia [ 92 , 135 , 136 ]. Furthermore, the protection of BBB and BRB help preserves the microenvironment at the injured site from disruption by systemic immunity and secondary inflammatory responses caused by degeneration.…”
Section: Pathways Targeted By Baicalein Baicalin and Wogonin During Neuroprotective Processesmentioning
confidence: 99%